First Application of Fecal Microbiota Transplantation in Adult Asperger Syndrome With Digestive Symptoms—A Case Report - Huang, Hong-Li; Xu, Hao-Ming; Liu, Yan-Di; Shou, Di-Wen; Chen, Hui-Ting; Nie, Yu-Qiang; Li, Yong-Qiang; Zhou, Yong-Jian (Frontiers in Psychiatry, 2022)
Asperger syndrome (AS) is a chronic neurodevelopmental disorder. Although all of the clinically diagnosed cases display normal intelligence and speech functions, barriers in social interaction and communication seriously affect mental health and psychological function. In addition to traditional psychological/behavioral training and symptomatic medication, in-depth studies of intestinal microbiota and mental health have indicated that probiotics (e.g., Lactobacillus rhamnosus) can effectively reduce the occurrence of AS. Fecal microbiota transplantation (FMT) is a type of biological therapy that involves the transplant of intestinal microbiota from healthy donors into the patient’s gastrointestinal tract to improve the gut microenvironment. In this case report, we describe the first case of adult AS treated with FMT. The patient suffered from diarrhea-predominant irritable bowel syndrome for six years with symptoms of diarrhea and abdominal pain. After three rounds of FMT, the diarrhea and abdominal pain were significantly improved. Moreover, the symptoms of AS were also significantly ameliorated. We found that FMT changed the structure of the intestinal microbiota as well as the patient’s serum metabolites, and these changes were consistent with the patient's symptoms. The metabolites may affect signaling pathways, as revealed by Kyoto Encyclopedia of Genes and Genomes enrichment analysis. The changes in microbial metabolites following FMT may affect other regions (e.g., the nervous system) via the circulatory system, such that the bacteria-gut-blood-brain axis may be the means through which FMT mitigates AS.